2011
DOI: 10.1093/jac/dkr360
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of efavirenz are associated with body weight in HIV-positive individuals

Abstract: In this cohort of well-controlled HIV-positive individuals, patients with lower weight or body mass index had a higher chance of presenting elevated plasma concentrations of efavirenz. Therapeutic drug monitoring to adjust dose might be a helpful tool to decrease efavirenz dose in order to minimize costs and adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 9 publications
4
25
3
Order By: Relevance
“…Plasma concentration average of our population was 6,360 µg/L ± 539 µg/L. It is definitely higher than those found by Poeta and Wyen, which were respectively 2,200 and 2,077µg/L [15][16]. In the studies preceding ours, plasma concentrations averages were included in the therapeutic index described [1,000-4,000 µg/L].…”
Section: Efavirenz Plasma Concentrationscontrasting
confidence: 52%
See 1 more Smart Citation
“…Plasma concentration average of our population was 6,360 µg/L ± 539 µg/L. It is definitely higher than those found by Poeta and Wyen, which were respectively 2,200 and 2,077µg/L [15][16]. In the studies preceding ours, plasma concentrations averages were included in the therapeutic index described [1,000-4,000 µg/L].…”
Section: Efavirenz Plasma Concentrationscontrasting
confidence: 52%
“…Stohr et al had found that a high weight induced a weak plasmatic concentration of EFV [5]. Brazilian study of Poeta et al [15] in 2011 had also revealed that high BMI induced weak level concentration of EFV (p = 0.001) [15]. Also, high BMI can mean a great drug distribution volume and thus, low plasma concentration.…”
Section: Plasma Concentrations and Socio-demographic Factorsmentioning
confidence: 99%
“…Several studies have demonstrated that a higher weight were associated with lower efavirenz levels [5], [6], but how to adjust doses according to the weight remains a debatable issue. Some studies suggested an increase of efavirenz dose for heavy patients taking rifampicin [26], while other studies showed data arguing against this suggestion [10], [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, multivariate analysis (n = 41) indicated that efavirenz concentrations show a significant (p = 0.015) inverse relationship with body weight through. 21 …”
Section: Discussionmentioning
confidence: 99%